Sound Propagation through the Stochastic Ocean. - Colosi, John A. (Cambridge University Press, 2016)
Key discoveries in the field of statistical ocean acoustics over the last 35 years are addressed with illustrations from ocean observations.
4.2.1 Ray/Internal Wave Resonance and Diffraction.
Keywords: Underwater acoustics.; Sound -- Transmission.; Oceanography.; elektronické knihy; electronic books